Relationship Between Wintertime Atmospheric Particulate Matter and Meteorological Conditions in Diyarbakir (Turkey) - ERDOGAN, SAIT; BAYSAL, AKIN; AKBA, OSMAN; MERDIVAN, MELEK; HAMAMCI, CANDAN (Asian Journal of Chemistry, 2010)
This paper reported the changes in pollution concentration in Diyarbakir, Southeast region of Turkey in the winter half of the year from 1986 to 2004 and describes the relationships with meteorology. Particulate matter (PM)10 is used as the example pollutant. Decrease in air pollution since 1994 was observed due to air pollution control and management strategies. The winters of 1988-1989, 1989-1990, 1990-1991, 1991-1992 and 1992-1993 were especially harsh in the number of pollution episodes.Linear regression results show that relative humidity and temperature provide the relationship with PM10 concentration.